Strategi Intervensi Peningkatan Kualitas Hidup Orang dengan HIV/AIDS - Ahmad, Zunaidi; Upoyo, Arif Setyo; Purnawan, Iwan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Quality of life in people with HIV/AIDS is influenced by various factors, including stigma, adherence to antiretroviral therapy, and social support. The aim of this study was to synthesize interventions that have been implemented to improve quality of life in people with HIV/AIDS based on recent primary research. This systematic review included articles published between January 2018 and August 2022, retrieved from seven databases: ScienceDirect, SAGE Journals, EBSCOHost, PubMed, Scopus, ProQuest, and Wiley Online. Inclusion criteria included randomized controlled trials involving people with HIV/AIDS, articles in English, and full-text submissions. Of the 965 articles identified, 10 met the inclusion criteria. Reported interventions included telemonitoring, yoga, cognitive behavioral therapy, community empowerment, and social support. Most interventions demonstrated a positive impact on quality of life, particularly in the psychological, social, and spiritual domains. The interventions lasted three to six months, with better outcomes in longer-term programs. Family involvement and interdisciplinary collaboration were concluded as key contributing factors to the success of the interventions.Keywords: people with HIV/AIDS; quality of life; antiretroviral therapy; social support ABSTRAK Kualitas hidup pada orang dengan HIV/AIDS dipengaruhi oleh berbagai faktor, termasuk stigma, kepatuhan terhadap terapi antiretroviral, dan dukungan sosial. Tujuan studi ini adalah mensintesis berbagai intervensi yang telah diterapkan untuk meningkatkan kualitas hidup pada orang dengan HIV/AIDS berdasarkan penelitian primer terbaru. Tinjauan sistematis ini mencakup artikel yang diterbitkan antara Januari 2018 hingga Agustus 2022, yang didapatkan dari tujuh database yaitu ScienceDirect, SAGE Journals, EBSCOHost, PubMed, Scopus, ProQuest, dan Wiley Online. Kriteria inklusi meliputi randomized controlled trial dengan melibatkan orang dengan HIV/AIDS, artikel berbahasa Inggris dan memuat teks lengkap. Dari 965 artikel yang diidentifikasi, 10 artikel memenuhi kriteria inklusi. Intervensi yang dilaporkan meliputi telemonitoring, yoga, cognitive behavioral therapy, pemberdayaan komunitas, dan dukungan sosial. Sebagian besar intervensi menunjukkan dampak positif pada kualitas hidup, terutama dalam domain psikologis, sosial, dan spiritual. Durasi intervensi adalah tiga hingga enam bulan, dengan hasil yang lebih baik pada program jangka panjang. Disimpulkan bahwa keterlibatan keluarga dan kolaborasi lintas disiplin menjadi faktor pendukung utama keberhasilan intervensi.Kata kunci: orang dengan HIV/AIDS; kualitas hidup; terapi antiretroviral; dukungan sosial